EFEK PEMBERIAN TEMULAWAK TERHADAP BERAT BADAN DAN SISTEM IMUN MENCIT BALB/c - Jap Lucy; Lulu Florencia; Elvina Elvina; Dina Stefani; Agustina Ika Susanti (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2017)
ABSTRACT.   Curcuma (Curcuma xanthorrihiza) is a well-known Indonesian traditional medicine. It is believed to be beneficial for health. Curcuma xanthorrihiza contain curcuminoid, starch and essential oil. This herb is widely used as a traditional medicine that is packaged in the form of powders, drinks and tablets. Curcuma xanthorrihiza tablet used in the study was separated by Thin Layer Chromatography (TLC) which exhibit the compound's content to be similar to pure curcuma. This study was followed by feeding BALB/c mice with curcuma tablet on different doses (100 mg / kg body weight (BW), 200 mg / kg, and 400 mg / kg and water as a control. The effect of various doses of Curcuma xanthorrihiza on weight gain and immune response was determined. Treatment was given to BALB/c mice for 20 days on different doses and weighed once a week. Observation of body weight of mice for four weeks showed that administration of Curcuma xanthorrihiza did not affect weight gain significantly (p < 0,05). Phagocytosis test and hemagglutination test (HA) were conducted, exhibiting both pro and anti-inflammatory actions.Keywords : adaptive, curcuma xanthorrihiza, hemagglutination, innate, phagocytosis